Literature Study: Happiness Learning in Class Using Media of Game-Based Learning - Auwlya, Fhadila; Quraishi, Tamanna (MANDALIKA : Journal of Social Science, 2025)
Traditional games are owned by a group of people, in which the game adheres to the norms and customs of the community which are passed down from their ancestors to the next generation. This study aims to describe the role of traditional games as interactive learning media to instill character education in elementary school students. Character education in traditional games contains values ​​of honesty, enthusiasm, courtesy, responsibility, cooperation, discipline, hard work, helping, never giving up, and so on. The methods used in this research are literature study, searching, analyzing, and drawing conclusions. The results obtained in this study indicate that traditional games can instill character education such as religion, honesty, enthusiasm, courtesy, responsibility, cooperation, discipline, sportsmanship, hard work, help, never giving up, and many more. Therefore, it is important to re-instill traditional games for children as learning media that can build good character in children. The Indonesian Child Protection Commission noted that 34% of children experienced legal cases and one of the cases was caused by bullying due to a lack of tolerance between individuals or social sensitivity from the very beginning. Therefore, teachers prepare themselves through learning that provides a safe and comfortable environment for students, especially students according to their growth and development. Learning that can increase student comfort is fun learning with a learning process using games or game media. Through a safe and comfortable learning process combined with games, students can gain optimal knowledge in both cognitive aspects such as reading, writing, and communicating